2015
DOI: 10.1039/c5ra11231a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of calcium oxalate with novel hierarchical structures mediated by amphiphilic phosphoproteins and its adsorptive removal of Congo red from aqueous solution

Abstract: Here, we developed a facile and green method to fabricate porous double cashew-shaped calcium oxalate (CaOx) in the presence of amphiphilic phosphoproteins. The obtained CaOx exhibits high efficient and selective adsorption of Congo red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Completely different morphology and crystal types were obtained in comparing with the previous study. 25,39 Casein (ranging from 0.1 g L À1 to 4.0 g L À1 ) induced changes in the crystal morphology as well as crystal form (Fig. 4 and 5).…”
Section: Inuence Of Small Molecular Additives On Mineralization Of Commentioning
confidence: 99%
See 3 more Smart Citations
“…Completely different morphology and crystal types were obtained in comparing with the previous study. 25,39 Casein (ranging from 0.1 g L À1 to 4.0 g L À1 ) induced changes in the crystal morphology as well as crystal form (Fig. 4 and 5).…”
Section: Inuence Of Small Molecular Additives On Mineralization Of Commentioning
confidence: 99%
“…Liu et al reported the production of dumbbell-shaped CaO x in the presence of amphiphilic phosphoproteins. 25,39 They investigated effects of casein on the morphogenesis of CaO x at pH 6.9 at room temperature. However, this condition is different to that in vivo.…”
Section: Inuence Of Small Molecular Additives On Mineralization Of Commentioning
confidence: 99%
See 2 more Smart Citations